OP0237 The Use of Positron Emission Tomography (PET) in Patients with Giant Cell Arteritis (GCA): Analysis of Data from the Diagnostic and Classification Criteria for Vasculitis (DCVAS) Study. (9th June 2015) - Ponte, C.; Rodrigues, A.F.; Prieto-González, S.; Alba, M.A.; Geraldes, R.; Craven, A.; Judge, A.; Grayson, P.C.; Suppiah, R.; Robson, J.; Watts, R.A.; Merkel, P.A.; et al.
Abstract : Background: Extracranial involvement in GCA, or "large-vessel GCA", has been described in 30-80% of cases, varying according to the imaging modality performed. PET is a sensitive test to detect extracranial inflammation (reported in up to 83% of the cases) and an association between the intensity of FDG uptake and clinical and laboratory features, such as acute phase reactants, has been described. Objectives: To assess the proportion of positive PET amongst patients with a diagnosis of GCA who were included in the DCVAS study, a multinational observational study to develop diagnostic criteria and update classification criteria for primary vasculitis, and to explore the relationship between the presence of increased FDG uptake and different clinical and laboratory findings. Methods: We included all patients recruited into DCVAS through September 2014 with a submitted diagnosis of GCA and 6-month follow-up data who underwent PET/PET-CT. A positive PET was defined as increased FDG-uptake in large vessels. We accepted the limitation of not knowing the reason for requesting the scan or the previous duration and dose of glucocorticoid treatment. Clinical features of patients with positive or negative PET were compared using Chi-square or Fisher exact tests; laboratory results and demographic features were analysed through logistic regression models Results: GCA was diagnosed in 442 patients; 87 (19.7%) underwent PET/PET-CT: 71 (81.6%) showed a positive result. The mean age in the positive PET group was 68.7±9.2 years vs. 71.5±9.0 years in the negative PET group, p=0.290. The table shows that new-onset headache was less frequent in patients with positive PET (p=0.004), but no significant associations were found with other common clinical features of GCA. Of 87 patients who underwent PET, only 49 performed TAB (31 with positive result); 46 of these 87 (52.9%) patients met the ACR classification criteria and were significantly more likely to having a negative PET (p=0.014). Logistic regression models showed no significant associations between ESR or CRP values and the presence of FDG uptake (p=0.374; p=0.17). Conclusions: PET is an increasingly utilized test for patients with GCA and is positive in a large percentage of cases. Patients with GCA and a positive PET frequently did not have a positive TAB result or fulfil ACR criteria for GCA, suggesting that PET may be useful in cases where diagnosis is uncertain and/or PET has expanded the range of patients that experts label as having GCA. Disclosure of Interest: None declared